Pemberdayaan Pemberdayaan Kelompok Tani Desa Semanggi dalam Pemanfaatan Limbah Pertanian Berupa Janggel Jagung Menjadi Briket - Fitriani, Anis (LPPM Stikosa - AWS, 2023)
Semanggi Village is a village in Jepon District, Blora Regency, Central Java. Semanggi Village has considerable potential for corn farming, but the agricultural waste itself is not utilized properly, such as corn cobs which are simply thrown away in the neighborhood where the community lives. This will have a bad impact on the environment if not utilized. Therefore, the Semanggi Village KKNT team created the SKS (Sesarengan Kumpul Sedulur) program which is a forum for the people of Semanggi Village to add insight as well as skills in processing agricultural waste in the form of corn cobs into environmentally friendly briquettes. With this program, it is hoped that it can reduce and overcome the problem of waste in Semanggi Village by processing it into products that have a sale value and can improve the economy of the surrounding community.